Is freeze-drying an alternative to solvent exchange for the hydration stop of cementitious suspensions?. (September 2022) - Kißling, Patrick A.; Lübkemann, Franziska; Mundstock, Alexander; Lohaus, Ludger; Haist, Michael; Caro, Jürgen; Bigall, Nadja C.
Abstract: In order to understand the rheological properties of cementitious suspensions at early stages, among other phases, the formation of ettringite and its time-dependent influence, whether by amount or morphology, has to be examined in detail using a suitable method to stop the hydration process. It is state-of-the-art to exchange water with isopropanol, however, the water initially remains in the system possibly leading to reduced time resolution. Our group raised the question if freeze-drying or the combination of the water-isopropanol exchange with subsequent freeze-drying might be a suitable technique to achieve an almost complete hydration stop at any time. Recently, it was shown under which circumstances low-pressure characterization techniques can be employed without destroying the samples due to loss of crystal bound water. Here, by implementing these recent results, we show under which circumstances freeze-drying indeed can be employed as fast hydration stop method.